Characterization of white matter over 1–2 years in small vessel disease using MR-based quantitative susceptibility mapping and free-water mapping - Sun, Yawen; Hu, Ying; Qiu, Yage; Zhang, Yuyao; Jiang, Changhao; Lu, Peiwen; Xu, Qun; Shi, Yuting; Wei, Hongjiang; Zhou, Yan (Frontiers in Aging Neuroscience, 2022)
Purpose: The aim of this study was to investigate alterations in white matter lesions (WMLs) and normal-appearing white matter (NAWM) with small vessel disease (SVD) over 1-2 years using quantitative susceptibility mapping (QSM) and free-water (FW) mapping. Methods: Fifty-one SVD patients underwent MRI brain scans and neuropsychological testing both at baseline and follow-up. The main approach for treating these patients is the management of risk factors. Quantitative susceptibility (QS), fractional anisotropy (FA), mean diffusivity (MD), FW, FW-corrected FA (FAT) and FW-corrected MD (MDT) maps within WMLs and NAWM were generated. Furthermore, the JHU-ICBM-DTI label atlas was used as an anatomic guide, and the measurements of the segmented NAWMs were calculated. The average regional values were extracted, and a paired t test was used to analyze the longitudinal change. Partial correlations were used to assess the relationship between the MRI indices changes ( e.g., ΔQSfollowup-baseline/QSbaseline) and the cognitive function changes (e.g.,ΔMoCAfollowup-baseline/MoCAbaseline). Results: After SVD risk factor control, no gradual cognitive decline occurred during 1-2 years. However, we still found that the QS values (index of demyelination) increased in the NAWM at follow-up, especially in the NAWM part of the left superior frontal blade (SF), left occipital blade, right uncinate fasciculus, and right corticospinal tract (CST). FW (index of neuroinflammation/oedema) analysis revealed that the follow-up group differed from the baseline group in the NAWM part of the right CST and inferior frontal blade (IF). Decreased FAT (index of axonal loss) was observed in the NAWM part of the right SF and IF at follow-up. In addition, the FAT changes in the NAWM part of the right IF were associated with overall cognitive performance changes. In contrast, no significant differences were found in the WMLs. Conclusions: The NAWM was still in the progressive injury process over time, while WMLs remained relatively stable, which supports the notion that SVD is a chronic progressive disease. The process of axonal loss in the NAWM part of the prefrontal lobe might be a biomarker of cognitive changes in the evolution of SVD.